Pengaruh Pendapatan Operasional terhadap Laba Bersih pada Bank Muamalat Indonesia Tbk. Periode 2015-2020 - Evita Septiani Jaenab; Ghina Fatimatuzzahro; Salsabila Gita Tsanya; R. Deden Adhianto (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
This study aims to determine the effect of operating income on net income at Bank Muamalat Indonesia Tbk. The period 2015 to 2020. The research method used is an associative quantitative method using secondary data in the form of the financial statements of Bank Muamalat Indonesia which are publicly registered with the Financial Services Authority. Hypothesis testing using simple linear regression analysis through t-test with a view to knowing the effect of independent variables on the dependent variable. The results of this study that the Operating Income variable on Net Profit has a correlation value or relationship (R) of 0.856 (Very Strong), and the value of the Determination Coefficient or R Square of 0.732 in other words the effect is 73.2%, meaning that the X variable (Operational Income) has an effect on on the variable Y (Net Profit) at Bank Muamalat Indonesia Tbk. While the remaining 26.8% is determined by other variables not examined by researchers, namely Non-Operational Income.